Java bing fa bian cheng shi zhan Java concurrency in practice / Brian Goetz [and six others] = Java concurrency in practice - Goetz, Brian (Hua zhang zhuan ye kai fa zhe cong shu, 2021)
Detailed summary in vernacular field.